The Application of Nature-Based Early Childhood Education Curriculum - Nurul Azizah; Nurul Ismaiyah; Khoirun Nisa (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2023)
The nature-based curriculum is applied at PAUD in every learning activity daily by considering the situation and conditions, including the weather on the implementation day. The nature-based curriculum is considered effective enough to achieve learning objectives; teachers can easily stimulate six early childhood development aspects. Aspects of early childhood development that experience significant development are in the physical, motoric, and cognitive aspects; it is shown by the development of students who are increasingly proficient in using accomplices during activities. Meanwhile, in the cognitive aspect of early childhood, it is easier to remember what the teacher conveys because they have direct experience. This type of research is a library qualitative approach that obtains data sources through library information such as books, scientific journals, magazines, newspapers, and documents. Data triangulation was done by triangulating sources and techniques through interviews and documentation. This research aims to determine the implementation of early childhood education activities with a nature-based curriculum based on the principles of nature-based learning. The results of this study are the implementation of children's learning with a nature-based curriculum in accordance with the principles and stages of nature-based learning.